Efficacy of different methods of inoculation for inducing root rot disease in castor caused by Macrophomina phaseolina: Efficacy of different methods of inoculation for inducing root rot disease in castor caused by Macrophomina phaseolina - PINAL VEKARIYA; A G DESAI (Journal of Oilseeds Research, 2020)
Soil inoculation and root dip inoculation methods were found more efficient, rapid and effective for identifying castor genotypes against root rot disease for early detection of resistance source. The soil inoculation method induced maximum (87.7%) root rot disease and was statistically at par with root dip inoculation method (82.7%) after 25 days of inoculation.